On the Seamlessness of Trees - Margaritis, Charalambos (My University, 2022)
A multimedia installation which presents a set of animated sequences, as well as a set of sound effects, in random order, thus generating a different narrative outcome each time it is seen by a spectator. The installation examines the possibilities of non-linear and multi-linear narration in animated film with the use of new technologies.
Keywords: Animation; Installation; Multimedia